2021
DOI: 10.1590/1678-992x-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of banana plantlets acclimatization by hydroponic cultivation

Abstract: Acclimatization is the final phase of banana plantlet production by micropropagation.In this phase, the plantlets are grown in a protected environment with high demand for water, fertilizer and labor, until reaching the standard size and quality required for marketing. The aim of this study was to evaluate the possibility of reducing these costs and the duration of the acclimatization phase, using the hydroponic cultivation technique as compared to the conventional system. 'Prata-Anã' banana plantlet performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Thus, the use of a longer interval of recirculation of nutrient solution in the first days of acclimatization of seedlings can be a viable strategy, because no significant difference in plant height and leaf area was found at 15 and 20 DAT. Toyosumi et al (2020) found significant differences between conventional and hydroponic systems for the acclimatization process of banana seedlings only after 20 days, with evaluations carried out every 5 days.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Thus, the use of a longer interval of recirculation of nutrient solution in the first days of acclimatization of seedlings can be a viable strategy, because no significant difference in plant height and leaf area was found at 15 and 20 DAT. Toyosumi et al (2020) found significant differences between conventional and hydroponic systems for the acclimatization process of banana seedlings only after 20 days, with evaluations carried out every 5 days.…”
Section: Resultsmentioning
confidence: 92%
“…Then, the treatments were applied. The experiment was conducted as described by Toyosumi et al (2020), using the nutrient film technique (NFT) adapted with the method of capillary action (Sardare & Admane, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation